Transition from sexuality to androgenesis through a meiotic modification during spermatogenesis in freshwater Corbicula clams. - Emilie Etoundi; Martin Vastrade; Clothilde Berthelin; Kristell Kellner; Mélanie Fafin-Lefèvre; Karine Van Doninck (PLoS ONE)
Asexual taxa are often considered as rare and vowed to long-term extinction, notably because of their reduced ability for rapid genetic changes and potential adaptation. The rate at which they derive from sexual ancestors and their developmental mode however influence genetic variation in asexual populations. Understanding the transition from sexuality to asexuality is therefore important to infer the evolutionary outcome of asexual taxa. The present work explored the transition from sexuality to androgenesis, a reproductive mode in which the males use female resources to clone themselves, in the freshwater Corbicula clams. Since androgenetic lineages are distinguishable from sexual clams by the production of unreduced sperm, this study investigated the cytological mechanisms underlying spermatogenesis in Corbicula by following the DNA content variation of male germ cells. The widespread androgenetic C. sp. form A/R lineage was compared to the sexual species C. japonica and C. sandai. While in C. japonica, the last stages of spermatogenesis are reduced through a canonical meiosis process, no reduced or duplicated stages were observed in C. sp. form A/R, suggesting a meiosis modification in this lineage. However, 45% of C. sandai spermatozoa were unreduced. The production of unreduced sperm may condition or provide the potential for the emergence of androgenesis in this sexual species. Being closely related to androgenetic lineages and found in sympatry with them in Lake Biwa (Japan), C. sandai might be an origin of androgenetic lineage emergence, or even an origin of the androgenetic reproductive mode in Corbicula.